Effects of Angiotensin-Converting Enzyme Inhibition on Circulating Endothelial Progenitor Cells in Patients with Acute Ischemic Stroke - Monika Gołąb-Janowska; Edyta Paczkowska; Bogusław Machaliński; Dariusz Kotlęga; Agnieszka Meller; Krzysztof Safranow; Michał Maj; Przemysław Nowacki (Hindawi Limited, 2018)
Background. Therapeutic neovascularization might represent an important strategy to salvage tissue after ischemia. Circulating bone marrow-derived endothelial progenitor cells (EPCs) were previously shown to augment the neovascularization of ischemic tissue. Angiotensin-converting enzyme inhibitors (ACEIs) might modulate EPC mobilization. We evaluated populations of circulating stem cells and early EPCs in acute ischemic stroke (AIS) patients and the effect of ACEI on circulating EPCs in these patients with respect to aspects of stroke pathogenesis. Methods. We studied 43 AIS patients (group I), comprising 33 treated with ACEI (group Ia) and 10 untreated (group Ib). Risk factor controls (group II) included 22 subjects. EPCs were measured by flow cytometry. Results. In AIS patients, the number of circulating stem cells and early EPCs upon admission was similar to that in control group individuals. There were no significant differences in the numbers of stem cells and early EPCs over subsequent days after AIS. There were also no significant differences in stem cell and early EPC numbers over the first 3 days between group Ia and group Ib. However, on day 7, these numbers were significantly higher in group Ib than in group Ia (p<0.05). In AIS patients chronically treated with ACEI, there was a negative correlation between CD133+ cell number and neurological deficit on the first, third, and seventh days (p<0.005). Conclusions. An increased number of circulating stem cells and early EPCs were not observed in stroke patients chronically treated with ACEI. In patients chronically treated with ACEI, a significant correlation was observed between decreased neurological deficit and higher levels of CD133+ cells; this could be due to the positive influence of these cells on the regeneration of the endothelium and improved circulation in the ischemic penumbra.